An environmental scan of emergency response systems and services in remote First Nations communities in Northern Ontario. Issue 1 (1st January 2017) - Mew, E. J.; Ritchie, S. D.; VanderBurgh, D.; Beardy, J. L.; Gordon, J.; Fortune, M.; Mamakwa, S.; Orkin, A. M.
ABSTRACT: Background : Approximately 24, 000 Ontarians live in remote Indigenous communities with no road access. These communities are a subset of Nishnawbe Aski Nation (NAN), a political grouping of 49 First Nations communities in Northern Ontario, Canada. Limited information is available regarding the status of emergency care in these communities. Objective : We aimed to understand emergency response systems, services, and training in remote NAN communities. Design : We used an environmental scan approach to compile information from multiple sources including community-based participatory research. This included the analysis of data collected from key informant interviews (n=10) with First Nations community health leaders and a multi-stakeholder roundtable meeting (n=33) in October 2013. Results : Qualitative analysis of the interview data revealed four issues related to emergency response systems and training: (1) inequity in response capacity and services, (2) lack of formalised dispatch systems, (3) turnover and burnout in volunteer emergency services, and (4) challenges related to first aid training. Roundtable stakeholders supported the development of a community-based emergency care system to address gaps. Conclusions : Existing first response, paramedical, and ambulance service models do not meet the unique geographical, epidemiological and cultural needs in most NAN communities. Sustainable, context-appropriate, and culturally relevant emergency care systems are needed.